2015
DOI: 10.1140/epja/i2015-15096-9
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic modulation of monochromatic neutrino beams

Abstract: A possibility to produce a modulated monochromatic neutrino beam is discussed. Monochromatic neutrinos can be obtained in electron capture by nuclei of atoms or ions, in particular, by nuclei of hydrogen-like ions. It is shown that monochromatic neutrino beam from such hydrogen-like ions with nuclei of non-zero spin can be modulated because of different probabilities of electron capture from hyperfine states. Modulation arises by means of inducing of electromagnetic transitions between the hyperfine states. Re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The high-resolution measurements of the spectrum of low energy outgoing electrons need the detectors with the ultra low threshold and background. The interesting concepts of various (monochromatic) ν e sources are also worth noticing [94][95][96][97][98][99]. A preliminary study on the feasibility of electron polarized scintillating GSO target has been carried out by [34].…”
Section: Discussionmentioning
confidence: 99%
“…The high-resolution measurements of the spectrum of low energy outgoing electrons need the detectors with the ultra low threshold and background. The interesting concepts of various (monochromatic) ν e sources are also worth noticing [94][95][96][97][98][99]. A preliminary study on the feasibility of electron polarized scintillating GSO target has been carried out by [34].…”
Section: Discussionmentioning
confidence: 99%
“…A list of isotopes with non-zero spins decaying only (I nEC = 1) or mainly (I nEC ≥ 0.98) by EC via allowed transition to a single final nuclear state is not too wide. Recently we composed such a list for Gamow-Teller transitions in the context of the problem of modulated neutrino beams formation [6] (see also [7]). Here we present an extended list of suitable isotopes that decay via Gamow-Teller transition into the ground or excited states of daughter nuclei; see Tables I and II.…”
Section: Suitable Isotopesmentioning
confidence: 99%
“…Proposals [1,2] for the EC based neutrino sources appeared as a part of a more general concept to use β-decaying nuclei (or ions with such nuclei) accelerated and accumulated in a storage ring to produce intense collimated neutrino beams (β beams) [3] (for more details on β beam projects, see [4,5]). With neutron-deficient nuclei decaying via β + or EC, one can form modulated completely or partially monochromatic neutrino beams (β and EC beams); such beams could be useful for neutrino oscillation experiments, as well as for other investigations in physics of the weak interaction (see [6,7] and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…Solving these equations we see that the speed 2 v of the bare nucleus before the absorption of a neutrino is given by the right hand side of Equation (8).…”
Section: Detection Of Neutrinos Using Bsibdmentioning
confidence: 99%
“…The directed neutrino beam can be switched and modulated by manipulation of the magnitude and direction of the magnetic field. It was also shown that electron capture beta-decay in hydrogen-like ions is extremely sensitive to the hyperfine interaction [4] [5] [6] [7] [8]. In fact, the decay from one of the hyperfine states can be completely forbidden.…”
Section: Introductionmentioning
confidence: 99%